MENGUAK KESADARAN MUZAKI DALAM MEMBAYAR ZAKAT PENGHASILAN - Kurniadi, Herdi; Auliyah, Robiatul; Wulandari, Anis (EKSPANSI, 2017)
Abstract: This study aims to uncover muzakiâs consciousness in paying zakat on income. This research is a qualitative study, using the transcendental phenomenological approach. The key informants in this study as many as three people of muzaki who had routinely pay zakat income more than five years. The results of the study showed that in general, the informant argues that income is one kind of the treasure (mal) which is obligated to be zakat issued. Whereas the ways to calculate the zakat, from three informants have similarity that equally counting on the gross income by using content of 2.5 percent. The next result showed that there is some consciousness that motivates the muzaki in paying zakat on income. The first consciousness is religiosity/faith. It is the obedience of informant in carrying out the obligation and the understanding of treasure concept in Islam; second, empathy for others, that the informant felt actuated to give the part of their income to others, especially to the nearby people; and third, the hope of a return, that the informant gave the part of their treasure because they want to get the requital. Keywords: Zakat on Income, Consciousness, Muzaki, the Way of Paying, Motivation